(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research starts from studying the contractual budget, which is one of the modern trends in preparing public budgets, both operational and capital, in addition to meeting the requirements of the global trend to achieve sustainable growth in all fields, whether financial or non-financial, and tools for the contractual budget have been identified (participation contracts, planning Implementation, monitoring) and studying its impact in supporting sustainable development through its dimensions (economic, social, and environmental). The method of the questionnaire was adopted as a main tool in collecting information on research variables and distributing it to a sample of (70) individuals who dictate positions of professional responsibility to achieve sustainable development. Within the directorates of the Ministry of Housing, Construction and Public Municipalities, a number of statistical methods were used for the purpose of analyzing the data for the answers of the research sample and testing hypotheses through the help of the statistical program (SPSS) then verifying the validity of the hypothesis from which the research was launched and based on the results of the analysis the research was concluded with a set of conclusions and recommendations The most important of which is the necessity to rely on modern methods in preparing public budgets and preparing a prior plan that is considered as a guide. Adopting it in preparing public budgets in the future, in addition to strengthening the direction of sustainable development in state ministries, considering that they protect the rights of future generations from the current wealth.